2016
DOI: 10.1371/journal.pone.0149050
|View full text |Cite
|
Sign up to set email alerts
|

Gene Regulatory Network Inference of Immunoresponsive Gene 1 (IRG1) Identifies Interferon Regulatory Factor 1 (IRF1) as Its Transcriptional Regulator in Mammalian Macrophages

Abstract: Immunoresponsive gene 1 (IRG1) is one of the highest induced genes in macrophages under pro-inflammatory conditions. Its function has been recently described: it codes for immune-responsive gene 1 protein/cis-aconitic acid decarboxylase (IRG1/CAD), an enzyme catalysing the production of itaconic acid from cis-aconitic acid, a tricarboxylic acid (TCA) cycle intermediate. Itaconic acid possesses specific antimicrobial properties inhibiting isocitrate lyase, the first enzyme of the glyoxylate shunt, an anapleroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 67 publications
3
62
0
1
Order By: Relevance
“…Since, IRG1 did not appear to be a direct miR93-target, we predicted that miR93 targets another gene that has the ability to modulate IRG1-expression. Recent report has shown that interferon regulatory factor (IRF)-1 can transcriptionally regulate IRG1-expression (34) and miRanda algorithm predicted that IRF1 and IRF9 are miR93-targets. qPCR analysis showed miR93-mimic did not decrease IRF1-expression (Supplement-23A,B); antagomir93 did not increase IRF1-expression (Supplemental Figure-23C,D) in normal or HSS-macrophages vs. controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since, IRG1 did not appear to be a direct miR93-target, we predicted that miR93 targets another gene that has the ability to modulate IRG1-expression. Recent report has shown that interferon regulatory factor (IRF)-1 can transcriptionally regulate IRG1-expression (34) and miRanda algorithm predicted that IRF1 and IRF9 are miR93-targets. qPCR analysis showed miR93-mimic did not decrease IRF1-expression (Supplement-23A,B); antagomir93 did not increase IRF1-expression (Supplemental Figure-23C,D) in normal or HSS-macrophages vs. controls.…”
Section: Resultsmentioning
confidence: 99%
“…While, the top 3 genes induced in miR106b-93-25 −/− ischemic-muscle (compared to WT) CXCL2 (50,51) , IRG1 (34,52) and GM3893 were intimately associated with immune responses (with the exception of GM3893, a long non-coding RNA) the top 3 downregulated genes C1QTNF3 (53) , MYH3 (54,55) and ACTC1 (56,57) were closely associated with skeletal muscle function. These data clearly indicated an inverse correlation between genes that regulate immune cell function and skeletal muscle perfusion-recovery in miR106b-93-25 −/− ischemic-muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Although itaconate has long been known to possess anti‐microbial properties, it was not known to be a mammalian‐derived metabolite until it was found in lung homogenates of mice infected with Mycobacterium tuberculosis and in cell lysates/supernatants from LPS‐treated macrophages . Subsequent studies identified that immune‐responsive gene 1 (IRG1), which is highly expressed in pro‐inflammatory macrophages, produces itaconate by catalyzing the decarboxylation of cis ‐aconitate, a TCA cycle metabolite . Given that IRG1 does not contain a formal mitochondrial targeting signal sequence, but is associated with the mitochondria, cis ‐aconitate is likely exported from mitochondria through a mitochondrial tricarboxylate transporter which then allows for conversion to itaconate in the cytosol by IRG1.…”
Section: Tca Cycle In Macrophage Polarizationmentioning
confidence: 99%
“…Similarly, upon binding to its receptor, progesterone promotes IRG1 mRNA production in pregnant mice, while knockdown of IRG1 impairs embryo attachment in vivo , suggesting that inducible expression of IRG1 is indispensable for successful blastocyst implantation . In addition, interferon regulatory factor‐1 has been identified as a positive regulator of IRG1 . Treatment of mouse BMDMs with LPS activates the interferon‐β/interferon regulatory factor‐1 signaling pathway and then upregulates IRG1 expression to enhance itaconate levels and trigger an anti‐inflammatory program.…”
Section: Physiological Roles and Regulation Of Irg1mentioning
confidence: 99%
“…36,37 In addition, interferon regulatory factor-1 has been identified as a positive regulator of IRG1. 38 Treatment of mouse BMDMs with LPS activates the interferon-b/interferon regulatory factor-1 signaling pathway and then upregulates IRG1 expression to enhance itaconate levels and trigger an antiinflammatory program. The resulting itaconate again inhibits LPS-induced interferon-b synthesis.…”
Section: Physiological Roles and Regulation Of Irg1mentioning
confidence: 99%